Multivariate discovery and replication of five novel loci associated with Immunoglobulin G N-glycosylation - Xia Shen (Nature Portfolio, 2017)
Multivariate analysis methods can uncover the relationship between phenotypic measures characterised by modern omic techniques. Here the authors conduct a multivariate GWAS on IgG N-glycosylation phenotypes and identify 5 novel loci enriched in immune system genes.